2013
DOI: 10.1002/macp.201300662
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behaviors of Poly(N‐isopropylacrylamide) Nanosized Hydrogel Particles/Poly(vinyl alcohol)/Water Systems: Effect of the Degree of Hydrolysis of PVA

Abstract: Using poly(vinyl alcohol) as a drug model, the swelling behaviors of thermosensitive poly(N‐isopropylacrylamide) gel with various concentrations of PVA are investigated. The swelling ratio in PVA9000 is larger than that of PVA89000 at the same composition because the fully hydrolyzed PVA acts as a steric hindrance. A lattice‐based molecular thermodynamic model is used to obtain interaction parameters and then directly applied to describe the swelling behaviors of the gel. Using only one adjustable parameter, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…As reported by Bae and co‐workers, addition of 15 wt% PVA with a M w of 9000 can reduce the VPTT of PNIPAM microgel by ≈2 °C, while 5 wt% PVA with a M w of 89 000 can decrease the VPTT by ≈4 °C. It is noteworthy that the PVA concentration used by Bae and co‐workers is three orders of magnitude higher than the PVA concentration used in the present study. When PVA concentration is low, its influence on the thermal behavior of PNIPAM microgel is actually negligible, as shown in Figure .…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…As reported by Bae and co‐workers, addition of 15 wt% PVA with a M w of 9000 can reduce the VPTT of PNIPAM microgel by ≈2 °C, while 5 wt% PVA with a M w of 89 000 can decrease the VPTT by ≈4 °C. It is noteworthy that the PVA concentration used by Bae and co‐workers is three orders of magnitude higher than the PVA concentration used in the present study. When PVA concentration is low, its influence on the thermal behavior of PNIPAM microgel is actually negligible, as shown in Figure .…”
Section: Resultssupporting
confidence: 57%
“…The fact that PVA, as a polymeric additive, can lower the phase transition temperature of PNIPAM and other thermosensitive polymers has been confirmed by many previous studies, in spite that the effect is usually quite faint . To test if the PVA chains can be adsorbed onto the microgel spheres, PVA was added to the microgel dispersions (P(NIPAM‐2‐AAPBA) or PNIPAM microgel, that is, sample a and b in Figure ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…30−33 It was reported that 5 wt % PVA can only decrease the VPTT of PNIPAM hydrogel by ∼4 °C. 31 Very differently, the VPTT of the surface layer of poly(N-isopropylacrylamide-co-2-acrylamidophenylboronic acid) (P(NIPAM-2-AAPBA)) microgel can be decreased by 8.4 °C in the presence of a very low concentration of PVA (only 0.004 wt %) because PVA can bind with PBA groups on the microgel surface and become close to PNIPAM chains. 28 Similarly, because glucose can bind with PBA groups in the P(NIPAM-2-AAPBA) microgel and become close to PNIPAM chains, it depresses the VPTT of P(NIPAM-2-AAPBA) microgel much more efficiently than the PNIPAM microgel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently found that the capability of an additive to shift phase transition temperature could be remarkably magnified by shortening the distance between the additive molecules and the thermosensitive polymer chains. , As a polymeric additive, poly­(vinyl alcohol) (PVA) can change the LCST/VPTT to a very small degree. It was reported that 5 wt % PVA can only decrease the VPTT of PNIPAM hydrogel by ∼4 °C . Very differently, the VPTT of the surface layer of poly­( N -isopropyl­acrylamide- co -2-acrylamido­phenylboronic acid) (P­(NIPAM-2-AAPBA)) microgel can be decreased by 8.4 °C in the presence of a very low concentration of PVA (only 0.004 wt %) because PVA can bind with PBA groups on the microgel surface and become close to PNIPAM chains .…”
Section: Introductionmentioning
confidence: 99%